2021
DOI: 10.3389/fonc.2021.710286
|View full text |Cite
|
Sign up to set email alerts
|

CXCL9 Is a Potential Biomarker of Immune Infiltration Associated With Favorable Prognosis in ER-Negative Breast Cancer

Abstract: The chemokine CXCL9 (C-X-C motif chemokine ligand 9) has been reported to be required for antitumour immune responses following immune checkpoint blockade. In this study, we sought to investigate the potential value of CXCL9 according to immune responses in patients with breast cancer (BC). A variety of open-source databases and online tools were used to explore the expression features and prognostic significance of CXCL9 in BC and its correlation with immune-related biomarkers followed by subsequent verificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Elevated CXCL9 level has been proved to be a good prognostic biomarker for the TNBC subgroup, while in the luminal A subgroup of patients, CXCL9 overexpression was correlated with poor prognostic characteristics 62 . Moreover, high CXCL9 expression has been related to improved survival in ER-negative BC 63 . We observed that higher CXCL9 expression appears to be associated with prolonged OS.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated CXCL9 level has been proved to be a good prognostic biomarker for the TNBC subgroup, while in the luminal A subgroup of patients, CXCL9 overexpression was correlated with poor prognostic characteristics 62 . Moreover, high CXCL9 expression has been related to improved survival in ER-negative BC 63 . We observed that higher CXCL9 expression appears to be associated with prolonged OS.…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale meta-analysis showed that clonal tumor mutation burden and CXCL9 expression were the strongest predictors of ICI responses across seven tumor types [ 42 ]. Liang et al reported that elevated levels of CXCL9 mRNA were associated with favorable outcomes in HR-negative breast cancer and CXCL9 was correlated with immune cell infiltration and immune-related biomarkers [ 43 ]. TIS score was developed as a predictive biomarker of ICIs from a large cohort of pembrolizumab-treated patients across nine different tumor types and the predictive utility of TIS score has been verified in many other studies [ 15 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study identified an abundance of myeloid cells expressing CXCL9, a cytokine induced by IFN-γ, in responders to atezolizumab and avelumab [ 46 ]. An analysis of clinical trial datasets for avelumab and atezolizumab showed a 2.4- and 2.8-fold increase in overall survival respectively for patients with the highest CXCL-9 expression compared to the lowest, which may be due to the CXCL9-CXCR3 axis promoting PD-L1 expression and increasing T cell recruitment [ 47 49 ]. This suggests a role for the analysis of other immune cells in the TME besides lymphocytes.…”
Section: Biomarkers In the Tumour Biopsy That Are Determined By Non-g...mentioning
confidence: 99%